A study on the influence of employee engagement attitudes and employee creativity and innovation at selected government linked companies (GLCs) / Nabila Huda Ibrahim - Ibrahim, Nabila Huda (2018)
Achieving national vision of 2020 requires for creativity and innovation of human capital. Employees are encouraged to be engaged for creativity and innovation. Transformational leadership style is also suggested by previous studies to play role in generation and implementation of novel ideas. The objectives of this study are to determine the level of employee creativity and innovation in selected Government Linked Companies (GLCs), examine the relationship of employee engagement attitudes and employee creativity and innovation and examine moderation role of transformational leadership in the relationship between employee engagement attitudes and employee creativity and innovation. The employee engagement attitudes in this study are involvement, empowerment and commitment. This study was quantitatively done with a total of 151 respondents at selected GLCs in Kuala Terengganu. PLS-SEM is employed as main data analysis. It was found that the level of employee creativity and innovation is high at GLCs, employee engagement attitudes which are employee empowerment and employee commitment is positively related with employee creativity and innovation. Meanwhile, the relationship between employee involvement and employee creativity and innovation is not supported. The moderation role of transformational leadership is also not supported. This study indicates that GLCs focus on employee creativity and innovation to increase organizational performance. This study highlights on the significance of employee engagement attitudes in employee creativity and innovation. This has added new knowledge for existing literature. Organization should invest for environment that could boost employee engagement.